2009
DOI: 10.1007/s00406-009-0046-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning in early-onset first-episode psychosis: comparison of diagnostic subgroups

Abstract: The aims of this study were to examine the nature and extent of cognitive impairment in first-episode early-onset psychosis (FE-EOP) soon after their stabilisation and to search for potential differences according to specific diagnostic sub-groups of patients. As part of a Spanish multicentre longitudinal study, 107 FE-EOP patients and 98 healthy controls were assessed on the following cognitive domains: attention, working memory, executive functioning, and verbal learning and memory. Three diagnostic categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 28 publications
2
31
1
Order By: Relevance
“…23,24 The discrepancy between the data showing cognitive impairment in bipolar disorder and close relatives [25][26][27][28] and the better premorbid cognitive functioning and scholastic performance in longitudinal studies in subjects who end up having adult bipolar disorder could be due to sample selection bias, medication, drug use, cognitive decline prior to the first psychotic episode, or other confounding factors. Reading difficulties and scholastic underachievement, however, seem to be more specific to early-onset schizophrenia than early-onset bipolar I disorder.…”
Section: Cognitive Impairment During Development In Schizophrenia Andmentioning
confidence: 99%
“…23,24 The discrepancy between the data showing cognitive impairment in bipolar disorder and close relatives [25][26][27][28] and the better premorbid cognitive functioning and scholastic performance in longitudinal studies in subjects who end up having adult bipolar disorder could be due to sample selection bias, medication, drug use, cognitive decline prior to the first psychotic episode, or other confounding factors. Reading difficulties and scholastic underachievement, however, seem to be more specific to early-onset schizophrenia than early-onset bipolar I disorder.…”
Section: Cognitive Impairment During Development In Schizophrenia Andmentioning
confidence: 99%
“…All patients received atypical anti-psychotic drugs, with which WM deficits have been associated [36,37]. However, WM deficits have been reported in untreated patients with schizophrenia, in patients about to begin treatment, and in patients at clinical onset of schizophrenia, as well as in healthy first-degree relatives of patients with schizophrenia [4,35,38,39]. The relationship between medication effects and WM is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Fitzgerald et al 10 compared earlyonset affective psychosis and early-onset schizophrenia (EOS), and patients with schizophrenia appeared to have more generalized impairment across cognitive functions. However, Zabala et al, 11 in a sample of adolescent psychosis, found no differences in terms of cognitive function impairment among schizophrenia, affective psychosis, and other psychoses.…”
Section: Introductionmentioning
confidence: 99%